Oral food challenges in pediatric food allergy: five-year experience of a level II hospital - Rodrigues, Inês Patrício; Rocha-Castro, Carlos; Bernardo, Miguel; Santos, Marinela; Matos, Clara; Monteiro, Tânia; Carvalho, Marisa; Quaresma, Márcia (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Introduction and Objectives: Oral food challenges (OFC) are the gold standard for the diagnosis of food allergy. The aim of this study was to characterize and analyze the OFCs performed in the Pediatric Department of the study hospital. Material and Methods: Retrospective analysis of all patients who underwent OFCs in the pediatric department of the study hospital from October 2016 to December 2021. All non-IgE-mediated reactions were excluded. Statistical analysis was performed using IBM Statistical Package for Social Sciences®. Results: A total of 301 OFCs were performed on a total of 172 patients during the study period. Most patients were preschool children (<6 years; 79.4%) and 40.1% had more than one OFC. The most frequently tested allergens were hen’s egg (26.2%), tree nuts (16.9%), and cow’s milk (16.7%). The positivity rate was 23.2%. Tests for milk and wheat were significantly associated with a positive result. The main reason for OFC testing was to establish a diagnosis (60.1%), but also to assess tolerance (25.6%) and to document the responsiveness threshold (14.3%). Most positive reactions were local/grade I (25.7%) or moderate/grade II (58.6%). Patients with a personal history of atopic comorbidities were more likely to have a positive test result (p=0.022), especially those with atopic dermatitis (p=0.022). Discussion and Conclusion: Most OFCs in this analysis were negative. Early recognition of food allergy resolution is essential to prevent unnecessary allergen avoidance. An increased risk of positive reactions to milk or wheat, or in the setting of a personal history of atopic dermatitis, should be considered.